2016
DOI: 10.1175/jamc-d-15-0182.1
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change Implications for Tropical Islands: Interpolating and Interpreting Statistically Downscaled GCM Projections for Management and Planning

Abstract: The potential ecological and economic effects of climate change for tropical islands were studied using output from 12 statistically downscaled general circulation models (GCMs) taking Puerto Rico as a test case. Two model selection/model averaging strategies were used: the average of all available GCMs and the average of the models that are able to reproduce the observed large-scale dynamics that control precipitation over the Caribbean. Five island-wide and multidecadal averages of daily precipitation and te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
50
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(52 citation statements)
references
References 49 publications
0
50
1
1
Order By: Relevance
“…More recently, other studies indicate that the frequency of drought and inter-annual variation in rainfall may also be increasing in the region [66,67]. As the climate changes in the Caribbean, wetter life zones may be replaced by drier life zones, as predicted for Puerto Rico based on analyses using model averaging of statistically downscaled general circulation models by IITF colleagues [68].…”
Section: Discussionmentioning
confidence: 98%
“…More recently, other studies indicate that the frequency of drought and inter-annual variation in rainfall may also be increasing in the region [66,67]. As the climate changes in the Caribbean, wetter life zones may be replaced by drier life zones, as predicted for Puerto Rico based on analyses using model averaging of statistically downscaled general circulation models by IITF colleagues [68].…”
Section: Discussionmentioning
confidence: 98%
“…, Khalyani et al. , Herrera and Ault ), few studies have considered how drought affects Caribbean forests (but see Burrowes et al. , Reyer et al.…”
Section: Discussionmentioning
confidence: 99%
“…, Khalyani et al. ). Results from experimental studies in the Amazon have found that tropical forests are highly vulnerable to multiyear drought (Nepstad et al.…”
Section: Introductionmentioning
confidence: 98%
“…In both cases, mean daily minimum temperature was more important than maximum temperature to explain fires. Given the projections that precipitation will decline in tropical islands including Puerto Rico and that this decline will cause increases in drought intensity [33], special care should be taken when selecting climatic variables for fire prediction models.…”
Section: Forest Ecology and Conservationmentioning
confidence: 99%
“…Lowland moist and montane forests are less susceptible to fires, though they can burn in dry years [25]. Understanding the relationship of current climate, landscape, and population can help predict the likelihood of increasing risk of fire occurrence in light of climate change projections in tropical islands [33]. Puerto Rico is an example from a tropical insular region where rapid and complex changes in land-use and land-cover (LULC) are occurring and where fire-prone ecosystems are being created [34,35].…”
Section: Introductionmentioning
confidence: 99%